Antimicrobial activity of nature-inspired molecules against multidrug-resistant bacteria - Hamad, Mohamad; Al-Marzooq, Farah; Srinivasulu, Vunnam; Sulaiman, Ashna; Menon, Varsha; Ramadan, Wafaa S.; El-Awady, Raafat; Al-Tel, Taleb H. (Frontiers in Microbiology, 2024)
Multidrug-resistant bacterial infections present a serious challenge to global health. In addition to the spread of antibiotic resistance, some bacteria can form persister cells which are tolerant to most antibiotics and can lead to treatment failure or relapse. In the present work, we report the discovery of a new class of small molecules with potent antimicrobial activity against Gram-positive bacteria and moderate activity against Gram negative drug resistant bacterial pathogens. The lead compound SIMR 2404 had a minimal inhibitory concentration (MIC) of 2 µg/mLl against methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-intermediate Staphylococcus aureus (VISA). The MIC values against Gram negative bacteria such as Escherichia coli and Actinobacteria baumanniiwere between 8-32 µg/mLl. Time kill experiments show that compound SIMR 2404 can rapidly kill tested bacteria. Compound SIMR 2404 was also found to rapidly kill MRSA persisters which display high levels of tolerance to conventional antibiotics. In antibiotic evolution experiments, MRSA quickly developed resistance to ciprofloxacin but failed to develop resistance to compound SIMR 2 2404 even after 24 serial passages. Compound SIMR 2404 was not toxic to normal human fibroblast at a concentration of 4 µg/mLl which is twice the MIC concentration against (MRSA). However, at a concentration of 8 µg/mLl or higher, it showed cytotoxic activity indicating that it is not ideal as a candidate against Gram negative bacteria. The acceptable toxicity profile and rapid antibacterial activity against MRSA highlights the potential of these molecules for further studies as anti MRSA agents.